Single PON network design with unconstrained splitting stages - Gouveia, L.; Lopes, M. J.; Sousa, A. (European Journal of Operational Research, 2015)
A Passive Optical Network (PUN) is a network technology for deploying access networks based on passive optical components. In a single PUN access network, the client terminals are connected to a Central Office through optical splitters and interconnecting fibers where each splitter splits in equal parts the input optical signal coming from the Central Office over its different output fibers. In this paper, we consider PUN topology solutions where the splitting ratio and the number of splitting stages are not constrained to a given target design but, instead, are decided based on the cost of the solutions. We present different Integer Linear Programming formulations to model this problem and provide computational results showing that the optimal solutions can be computed for realistic problem instances. In addition, we describe how the formulations can be adapted for the traditional PUN topology approaches and present computational results showing that significant cost gains are obtained with the unconstrained splitting stage approach.